2021
DOI: 10.11591/ijere.v10i1.20956
|View full text |Cite
|
Sign up to set email alerts
|

The use of reflective practice towards achieving effective English language teaching at primary schools

Abstract: <span>The purpose of this study was to explore the use of reflective practice by English language teachers in providing effective English language teaching in primary school classrooms. This qualitative case study involving six in-service English language teachers who were selected based on purposive sampling. The data in this study were collected using teachers’ reflection logs and a series of semi-structured interviews with the English language teachers. Thematic analysis was used to identify emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…Figure 3 shows the comparison. The findings align with the qualitative case study by Hashim and Yusoff [43] exploring the use of reflective practice by English language teachers which emphasized continuous learning, making connections through code-switching, and using students' prior knowledge.…”
Section: Language Learning Assessmentsupporting
confidence: 80%
“…Figure 3 shows the comparison. The findings align with the qualitative case study by Hashim and Yusoff [43] exploring the use of reflective practice by English language teachers which emphasized continuous learning, making connections through code-switching, and using students' prior knowledge.…”
Section: Language Learning Assessmentsupporting
confidence: 80%
“…According to more recent studies by Chung (2021) and Hashim and Yusoff (2021), which both explored the use and effectiveness of reflective dialogues in teaching professional growth, reflective dialogues could facilitate teachers to increase PCK knowledge through changes in their personal domain, like beliefs and attitude. More specifically, Chung (2021) investigated the role of dialogic reflections among Asian secondary school English language teachers and indicated that it should be viewed as an approach to teacher learning as teachers could enhance their understanding from self-reflection and others' reflections.…”
Section: Reflective Dialoguesmentioning
confidence: 99%
“…Self-efficacy and self-reflection have been shown to contribute to English learning success in the field of language learning. (Hashim & Mohd Yusoff, 2021;Khongput, 2020;Orakcı, 2021;Puspita et al, 2014). Thus, students need to apply self-efficacy and selfreflection in the teaching and learning process.…”
Section: Introductionmentioning
confidence: 99%